Implementation of Exemplary Leadership in the Unit Development in Arhanud 003/ARK Detachment, Cikupa, Tangerang - Sughoro, Sistra Bayu; Kutanegara, Pande Made; Listyaningsih, Umi (Center for Populatioan and Policy Studies Universitas Gadjah Mada, 2023)
The leadership role which prioritizes the element of exemplary behavior by the commander is essential in the implementation of unit development at Arhanud 003/ARK Detachment. This is related to unit members who are required to maintain their operational readiness to protect the unit against all increasing air attacks. Quantitative research conducted on all members of the Detachment aims to explore the implementation of Exemplary Leadership through practices (Model the Ways, Challenge the Process, Inspire a Shared Vision, Enable Others to Act, and Encourage the Heart) by the Commander in the unit development at the Arhanud 003/ARK Detachment and knowing the implementation of Exemplary Leadership from these five indicators which are the most influential in unit development at Arhanud 003/ ARK Detachment. Multiple regression analysis using the Stepwise method shows differences in the application of Exemplary Leadership according to Battery A, Battery B, Missile Platoon, and Maintenance Platoon. This condition has an impact on unit development at the Arhanud 003/ARK Detachment. The results of the analysis show that unit development is positively influenced by the implementation of Exemplary Leadership in the practices of Challenge the Process and Encourage the Heart, while other factors (Model the Ways, Inspire a Shared Vision, Enable Others to Act) are not that influential. This is because there are still obstacles and barriers in the unit development at the Arhanud 003/ARK Detachment which require innovative strategies and ideas as well as members who are always optimistic in improving the unit development at the Arhanud 003/ARK Detachment.